Clinical Efficacy and Openness to New Challenges of Low Dose Rate Brachytherapy for Prostate Cancer - Manabu Kato; Shinichiro Higashi; Yusuke Sugino; Shinya Kajiwara; Shiori Tanaka; Goshi Kitano; Yasuhumi Yamashita; Yuji Ogura; Hiroyuki Tachibana; Takahiro Kojima; Takahiro Inoue (Current Oncology, 2023)
Over a century ago, low-dose-rate (LDR) brachytherapy was introduced to treat prostate cancer (PCa). Since then, it has been widely applied worldwide, including in East Asia. LDR brachytherapy has been performed in 88 institutes in Japan. Beneficial clinical outcomes of LDR brachytherapy for intermediate-to-high-risk PCa have been demonstrated in large clinical trials. These clinical outcomes were achieved through advances in methods, such as urological precise needle puncture and seed placement, and the quantitative decision making regarding radiological parameters by radiation oncologists. The combined use of LDR brachytherapy with other therapeutic modalities, such as external beam radiation and androgen deprivation therapy, for the clinical risk classification of PCa has led to better anticancer treatment efficacy. In this study, we summarized basic LDR brachytherapy findings that should remain unchanged and be passed down in urology departments. We also discussed the applications of LDR brachytherapy for PCa in various clinical settings, including focal and salvage therapies. In addition, we highlighted technologies associated with brachytherapy that are under development.